On the computational complexity of the empirical mode decomposition algorithm - Wang, Yung-Hung; Yeh, Chien-Hung; Young, Hsu-Wen Vincent; Hu, Kun; Lo, Men-Tzung (Physica A, 2014)
It has been claimed that the empirical mode decomposition (EMD) and its improved version the ensemble EMD (EEMD) are computation intensive. In this study we will prove that the time complexity of the EMD/EEMD, which has never been analyzed before, is actually equivalent to that of the Fourier Transform. Numerical examples are presented to verify that EMD/EEMD is, in fact, a computationally efficient method. •The order of the computational complexity of the EMD is equivalent to FFT.•Optimized program is proposed to speed up the computation of EMD up to 1000 times.•Fast HHT with optimized EMD/EEMD algorithm can operate in real-time.